Perhitungan Pajak Penghasilan atas Usaha Katering (Studi Pada Katering SR) - Sanie Sabella; Dian Nirmala Dewi; Endang Asliana (Politeknik Negeri Lampung, 2021)
SR catering is a food and beverage provider that is equipped with equipment and equipment for the manufacturing, storage, and presentation process in accordance with the location of the order. In 2018, the Government issued Government Regulation No. 23 of 2018 on the change of the tax rate which was originally 1% to 0.5%. This writing aims to explain the implementation of tax obligations on SR Catering suggested by the Tax Consultant Office Z. The data used is in the form of sales recapitulation for the period january 2019, a certificate of Government Regulation No. 23 of 2018, Annual Tax Return, and proof of deposit. The analytical method used this final task is a qualitative descriptive method. The results of this writing show that SR Catering is subject to the tax rules of Government Regulation No. 23 of 2018 where SR Catering has a certificate stating that SR Catering has a certain gross circulation and is subject to Final Income Tax at a rate of 0.5% and in the implementation of its virginity SR Catering performs calculations, deposits, and reporting that has been in accordance with the government regulations.